Kurdi, Mária. Representations of Gender and Female Subjectivity in Contemporary Irish Drama by Women. Lewiston, Queenston, Lampeter: Mellen, 2010. 249 pp. - Bach, Anikó (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Mária Kurdi is author and editor of several books and of innumerable scholarly papers and essays related to Irish literature and theatre. Her fourth published book is entitled Representations of Gender and Female Subjectivity in Contemporary Irish Drama by Women. With this new book, Kurdi enriches the list of recent years’ critical writings that try to contest the view that the Irish theatre is the domain of male playwrights only. Kurdi’s book joins works like Gender and Modern Irish Drama (2002) written by Susan Cannon Harris, Melissa Sihra’s Women in Irish Drama: A Century of Authorship and Representation (2007), or critical articles of Cathy Leeney and Mary Trotter—to name only a few.